The golden statue of the goddess Anahit in the context of the artistic culture of ancient Armenia - Margaryan, Hasmik (ARAMAZD: Armenian Journal of Near Eastern Studies, 2018)
Many narratives on the temples and cult centres of ancient Armenia, particularly on the temples in the Euphrates and Aratsani river valleys are preserved in the Classical and Armenian early medieval written sources. One of the most significant temples was the temple of the goddess Anahit, located in the settlement Erez of the province of Acilisene. Acilisene’s land properties and political weight was so great that Pliny the Elder and Dio Cassius named this province after the temple Anaetica. This religious centre occupied one of the most important places among famous temples of Asia Minor, such as the temple of Anahit in Zela (in Comana Pontica) and the temple of Enyo-Ma in Comana Cappadocia.